2017
DOI: 10.1111/cas.13282
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional therapy with α‐emitting trastuzumab against peritoneal metastasis of human epidermal growth factor receptor 2‐positive gastric cancer in mice

Abstract: Peritoneal metastasis of gastric cancer (PMGC) is incurable and thus has an extremely poor prognosis. We have found, however, that locoregionally administered trastuzumab armed with astatine‐211 (211At‐trastuzumab) is effective against human epidermal growth factor receptor 2 (HER2)‐positive PMGC in a xenograft mouse model. We first observed that 211At‐trastuzumab can specifically bind and effectively kill NCI‐N87 (N87) cells, which are HER2‐positive human metastatic GC cells, both in vitro and in s.c. tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…The body weights of the mice tended to be lower in the groups treated with both 211 At‐OTSA101 and 90 Y‐OTSA101 compared to the control mice, but no severe body weight loss was observed in the RIT groups and all varied within a normal range. Although hematological toxicities were not examined in our current experiments, our previous study showed transient but recoverable leukocytopenia following the systemic administration of an α‐emitting antibody …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The body weights of the mice tended to be lower in the groups treated with both 211 At‐OTSA101 and 90 Y‐OTSA101 compared to the control mice, but no severe body weight loss was observed in the RIT groups and all varied within a normal range. Although hematological toxicities were not examined in our current experiments, our previous study showed transient but recoverable leukocytopenia following the systemic administration of an α‐emitting antibody …”
Section: Discussionmentioning
confidence: 89%
“…Biodistribution studies were performed as described previously . Briefly, 111 In‐labeled OTSA101 ( 111 In‐OTSA101, 1 μCi) or 211 At‐OTSA101 (12.5 μCi) was injected into the tail veins of the SS xenograft mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they reported that HER2 overexpression and/or amplification may be a molecular abnormality linked to this disease development. [21] In addition to the abovementioned studies, Li et al [22] investigated the effectiveness of locoregionally administered trastuzumab armed with astatine-211 (211At-trastuzumab) against HER2 (+) peritoneal metastasis of gastric cancer in a xenograft mouse model. They concluded that locoregionally administered 211At-trastuzumab significantly prolonged the survival time of HER2 (+) peritoneal metastasis of gastric cancer mice compared with control treatments.…”
Section: Discussionmentioning
confidence: 99%